Difference in disease burden and activity in pediatric patients on brain magnetic resonance imaging at time of multiple sclerosis onset vs adults - Waubant, Emmanuelle; Chabas, Dorothee; Okuda, Darin T; Glenn, Orit; Mowry, Ellen; Henry, Roland G; Strober, Jonathan B; Soares, Bruno; Wintermark, Max; Pelletier, Daniel (Archives of neurology (Chicago), 2009)
To compare initial brain magnetic resonance imaging (MRI) characteristics of children and adults at multiple sclerosis (MS) onset. Retrospective analysis of features of first brain MRI available at MS onset in patients with pediatric-onset and adult-onset MS. A pediatric and an adult MS center. Patients with pediatric-onset <18 years) and adult-onset (> or =18 years) MS. We evaluated initial and second (when available) brain MRI scans obtained at the time of first MS symptoms for lesions that were T2-bright, ovoid and well defined, large (> or =1cm), or enhancing. We identified 41 patients with pediatric-onset MS and 35 patients with adult-onset MS. Children had a higher number of total T2- (median, 21 vs 6; P < .001) and large T2-bright areas (median, 4 vs 0; P < .001) than adults. Children more frequently had T2-bright foci in the posterior fossa (68.3% vs 31.4%; P = .001) and enhancing lesions (68.4% vs 21.2%; P < .001) than adults. On the second brain MRI, children had more new T2-bright (median, 2.5 vs 0; P < .001) and gadolinium-enhancing foci (P < .001) than adults. Except for corpus callosum involvement, race/ethnicity was not strongly associated with disease burden or lesion location on the first scan, although other associations cannot be excluded because of the width of the confidence intervals. While it is unknown whether the higher disease burden, posterior fossa involvement, and rate of new lesions in pediatric-onset MS are explained by age alone, these characteristics have been associated with worse disability progression in adults.